Nem que a vida os separe: dúvidas e prescrições sobre casamento nos Anos Dourados da revista O Cruzeiro (1946 a 1963) - Luciana de Moura Ribeiro (2012)
This research aimed at identifying, organizing and analyzing concerns, behaviors and values related to marriage, daily experienced in Brazil from the 1940s to the 1960s, reported by a female magazine section entitled "Woman to Woman" of the magazine O Cruzeiro. By knowing that the printed media is an inherent symbolic goods generator and an important disseminator of them thereby promoting social movement, it has a prominent role in this study. Accordingly, we chose the "Marriage" as the central theme of this investigation because, over time, this has been the cornerstone of relations between genders. The addressedsection was dedicated to dialogue with the female audience, presented in letter format to readers with straight and simple language as well as personal, whose aim was also to dispel doubts and guide behaviors. All sections recovered from the magazines are kept by the State Public Library Luiz de Bessa which joined an important material as a source of this research intended to understand the elements of such complex social relationships among female and male subjects. The documentary research was conducted along with a sample size of 231 articles (202 for female and 29 for male), contained in 212 magazines. The data were classified into eight categories, guided by content analysis and theoretical gender. The organization of the material constitutive analysis was performed with the aid of the software Nvivo 8. Results showed some persistence in traditional values of women as being responsible for the household, duties of wife, homemaker and motherhood, in accordance with the traditional identity, being the fulfillment of their tasks seen as the representation of the ideal woman. Regarding the representation of man, the results also demonstrated the preservation of historic sites, which made reference to the husband as breadwinner and maintainer of honor, keeping representation of man even as provider, which demonstrates the strength and endurance of this value. There are also harbingers of social change that would be glimpsed in later decades with regard to women. Therefore, it is clear that progress was made in discussions on topics of socialization of women in the previous decade. However, the representation of hegemonic ideal man still persists.